An Agenda for Best Practice Research on Group Singing, Health, and Well-Being. (8th July 2019) - Dingle, Genevieve A.; Clift, Stephen; Finn, Saoirse; Gilbert, Rebekah; Groarke, Jenny M.; Irons, J. Yoon; Bartoli, Alice Jones; Lamont, Alexandra; Launay, Jacques; Martin, Eleanor S.; Moss, Hilary; Sanfilippo, Katie Rose; et al.
Research on choirs and other forms of group singing has been conducted for several decades and there has been a recent focus on the potential health and well-being benefits, particularly in amateur singers. Experimental, quantitative, and qualitative studies show evidence of a range of biopsychosocial and well-being benefits to singers; however, there are many challenges to rigor and replicability. To support the advances of research into group singing, the authors met and discussed theoretical and methodological issues to be addressed in future studies. The authors are from five countries and represent the following disciplinary perspectives: music psychology, music therapy, community music, clinical psychology, educational and developmental psychology, evolutionary psychology, health psychology, social psychology, and public health. This article summarizes our collective thoughts in relation to the priority questions for future group singing research, theoretical frameworks, potential solutions for design and ethical challenges, quantitative measures, qualitative methods, and whether there is scope for a benchmarking set of measures across singing projects. With eight key recommendations, the article sets an agenda for best practice research on group singing.